SPORTS MANAGEMENT COMPARATIVE ANALYSIS OF FOUR PROFESSIONAL SOCCER TEAMS FROM SOUTHERN BRAZIL (Fiep Bulletin - online, 2014)
With world's and Brazilian soccer evolution, it is essential that professional clubs hire full time managers, working with administrative transparence in order to attract important sponsors and avoiding having just one income source. The present study was done with a semi-structured questionnaire aiming to investigate four southern Brazilian soccer teams, and revealed the following: the P team is the only one close to the revised literature suggestions, with its main income in television rights; the Q team needs structural and administrative upgrades, with its main income in club's associated members monthly fees. The R team has been under structural improvements and its main income is in the players' uniform. The S team has full time professional managers and its main income is in game tickets selling. The four teams' main expense is with soccer players' salary.
Keywords: soccer; sports management; management